2008
DOI: 10.1007/s10802-007-9156-x
|View full text |Cite
|
Sign up to set email alerts
|

Children with Autism and Their Friends: A Multidimensional Study of Friendship in High-Functioning Autism Spectrum Disorder

Abstract: This study of Israeli and American preadolescent children examined characteristics of friendship in 44 children with high-functioning autism spectrum disorder (HFASD) compared to 38 typically developing children (TYP), as they interacted with a close friend Participants were 8-12 years of age (HFASD: Israel, n = 24; USA, n = 20; TYP: Israel, n = 23; USA, n = 15), and were matched on SES, receptive language vocabulary, child age, and gender (each study group included one girl). Multidimensional assessments incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
116
3
6

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 157 publications
(137 citation statements)
references
References 38 publications
12
116
3
6
Order By: Relevance
“…This should be regarded as an encouraging finding and to some extent addresses the question of previous researchers (Bauminger, Solomon, Aviezer, Heung, Gazit, et al, 2008;Chamberlain, et al, 2007;Hurley-Geffner, 1995) whether the friendships of children with developmental disabilities look similar to friendships between typically developing children. In broad terms, there is evidence that for a majority of dyads, relationships were reported to possess the basic behavioral features associated with friendship, at least some of the time.…”
Section: Components Of Friendshipsupporting
confidence: 70%
See 1 more Smart Citation
“…This should be regarded as an encouraging finding and to some extent addresses the question of previous researchers (Bauminger, Solomon, Aviezer, Heung, Gazit, et al, 2008;Chamberlain, et al, 2007;Hurley-Geffner, 1995) whether the friendships of children with developmental disabilities look similar to friendships between typically developing children. In broad terms, there is evidence that for a majority of dyads, relationships were reported to possess the basic behavioral features associated with friendship, at least some of the time.…”
Section: Components Of Friendshipsupporting
confidence: 70%
“…Peer status measures, however, may not relate to actual shared activities or to friendship (e.g., Evans, et al, 1992;Hall & McGregor, 2000). While some researchers have described relationships of children with disabilities in inclusive settings as being very ordinary and characteristic of friendships between typically developing children (Staub, 1998;Strully & Strully, 1985), others have suggested that the friendships involving children with developmental disabilities may be different in quality or features (e.g., Bauminger, Solomon, Aviezer, Heung, Gazit, et al, 2008;Chamberlain, Kasari, & Rotherham-Fuller, 2007;Hurley-Geffner, 1995). Thus, it would seem probable that at least some relationships have a different character to those between typically developing children.…”
Section: Mutual Liking Enjoyment and Shared Interactions In The Clomentioning
confidence: 99%
“…The period of adolescence is a phase of life in which social relations are pressing and fundamental, and the difficulties in social area can thereby be increased [5,6,14,15,17,24]. Studies have been conducted in populations of young healthy controls [8,25,28].…”
Section: Introductionmentioning
confidence: 99%
“…Such Individuals tend to rely on logic, rules , patterns, and memory (Sahyoun et al 2009) as well as environmental and sensory information (O'Connor & Kirk 2008; Baron-Cohen 2000) in social interactions and tend to focus on scientific and analytical discussions, contributing new knowledge (Bauminger et al 2008), or discussing particular shared interests with similar minded friends. They may prefer to employ material culture or technology to communicate (Ochs and Solomon 2010;Grinker 2010) rather than engage in face-to-face sharing of narratives or emotional displays (Fitzgerald and O'Brien 2007;Baron-Cohen 2012).…”
Section: Autism Without Intellectual Impairment Is Associated With Vamentioning
confidence: 99%